THE ENVIRONMENT-FRIENDLY SMALL FARMERS AT THE CENTRAL HIGHLANDS OF MEXICO - Sergio R. Marquez-Berber; Cristina Torcuato-Calderon; Gustavo Almaguer-Vargas; Alma V. Ayala-Garay; Jorge Aguilar-Avila; Abdul K. Gardezi (European Scientific Journal, ESJ, 2015)
Conscious consumers demand better quality, and food locally produced with safety measures to have improved health and lower their carbon footprint. Regional ecology-friendly agriculture can fulfil such requirements. The objective of this paper is to present a case study of environment-friendly farmers in the State of Tlaxcala at the Central Highlands of Mexico, and the challenges that they have to confront. Groups of small farmers growing organic products created the Alternative Markets of Tlaxcala and Apizaco. The products sold in these markets are cultivated directly by 36 family groups, with an average of five members. They indirectly benefit another 150 people. Their plots are small, up to 5 hectares. They grow and sell temperate fruits, vegetables, cereal grains, honey and its derivate products. They also offer processed foods, handcrafts, personal hygiene products, and botanical goods. They use an alternative certification system, a participatory guarantee one. Since 2013, a plan of actions to consolidate the participative certification committee and to offer technical advice and training on organic production and food safety was conducted. The Alternative Markets have promoted the production and transformation of environment-friendly goods. They offer the option to sell products for higher prices than conventional ones. Consumers are willing to pay a premium for food and other items free from toxic agrochemicals, bought directly from the producers. The farmers and transformers of such markets are beginning to understand the importance to grow safe food and other products, and to implement procedures to achieve this objective.